Maize Production and Use - Hossain, Akbar (IntechOpen, 2020)
Maize is a staple cereal after wheat and rice. It is an important source of carbohydrate, protein, iron, vitamin B and minerals for many poor people in the world. In developing countries maize is a major source of income in resource-poor farmers. As maize is used both as silage and as crop residue and the grains of maize are usually used for food, starch and oil extraction industrially, the demand for maize is rising day by day. Therefore, it is imperative for improvement of maize to meet the increasing demand. This book entitled "Maize - Production and Use" highlights the importance of maize and the improved management approaches for improving the productivity of maize in the era of changing climate.